Prediction of real contact area on curvature region in hot stamping process of AA7075 aluminium sheet - Muhammad Amir Iqbal, Jefry; Mohamad Farid, Mohamad Sharif; Wahaizad, Safiei; Suraya, Sulaiman (Springer, 2024)
Hot stamping process of AA7075 aluminium sheet is one of the forming methods used to produce high-strength structural components for automobiles despite their poor room-temperature formability. In this method, the hot aluminium sheet (also known as blank) must be cooled rapidly to prevent the formation of coarse precipitate, which could compromise the strength of the component. The real contact area between two solid surfaces is crucial as it determines the amount of heat transfer from the hot aluminium blank and the cold steel die, thereby affecting the cooling rate of the component formed. This study will use finite element analysis to predict the real contact area between multiple asperities on a flat AA7075 blank surface and a curved, asperity-free steel die surface under different displacements and localized loads. The resulting real contact area could be correlated as a function of displacement and localized load, for used in ANSYS simulation.